Orientação profissional: atuação na formação humana integral de alunos da EPTNM - Ferreira, Samuel Anderson (2020)
The research aimed to understand in what aspects a Professional Guidance Program can act in the Integral Human Education of students of Technical Professional Education of Medium Level. This is a qualitative research that was developed through action research with graduate students of technical high school in which the professional guidance program focused on integral human training of students of the EPTNM was a pplied, having been, for the end of the research, the program structured in three stages: planning, implementation and evaluation (TRIP P , 2005). For data collection, participant observation techniques, sem istructured interviews and conversation wheel were used and, as instruments for data recording, audiovisual recording, field diary and written productions of th e partici pants. The method for interpreting the collected data was the Discursi ve Textual Analy sis (MORAES; GALIAZZI, 2006), in its three phases: unitarization; categorization; understanding or capture of the new emerging. The research generated as results three ca tegories: the various meanings of professional choice; the collective construction of crit ical sense; the process of building autonomy, w hich demonstrated that a Professional Orientation Program can act in Integral Human Formation in the aspects o f attribu tion of meaning to professional choice, in the construction of critica l sense and in t he d evelopment of autonomy. The research resulted i n the educational product: Professional Orientation Program: building Integral Human Training at EPTNM, which aims to contribute to the work of psychologists working in the EPTNM and favor the Integral Hum an Formation of students from federal institutes and other realities that develop the EPTNM, assisting in the decision making critical, conscious and reflective.